Development Of Zero One Integer Programming Model For Optimizing The Number Of And Location Firefighter Station In North Aceh Distric - Muhammad Zakaria; Syarifuddin Abdullah (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
Fires is a disaster that happened unexpectedly and caused huge losses in the form of casualties’ man and property. Fire is often unavoidable, which can be done is to minimize losses by establishing and providing firefighting facilities in the right area so as to reach the sub district center area in less than 15 minutes at the time of fire to extinguish the fire. At present North Aceh District has built 3 (three) fire stations to serve 27 sub-districts within its territory (Kantor Dinas Pemadam Kebakaran Kabupaten Aceh Utara). The existing fire stations are located in Alue Bili, District Nisam, District Landing Lhoksukon and Krung Mane, District Muara Batu. This study aims to determine the number and locations of the Optimal Firefighting Station within the district of North Aceh, which is a minimal number Stations but can reach all areas within the district of North Aceh. To achieve this goal, the method used is to model the problem into the Integer ZeroOne programming model, then completed with TORA windows® version 1.00 June 2002 by Taha H.. The implementations of the models produce the optimal solution is the minimum number of fire stations that must be built in North Aceh Regency is 6 stations so it needs to be added 3 more stations, with locations in the sub-district: Baktiya, Banda Baro, Cot Girek, Geureudong Pase, Kuta Makmur and Syamtalira Aron.